2007
DOI: 10.1128/aem.00662-07
|View full text |Cite
|
Sign up to set email alerts
|

Gliding Arc Discharge in the Potato PathogenErwinia carotovorasubsp.atroseptica: Mechanism of Lethal Action and Effect on Membrane-Associated Molecules

Abstract: . This prototype also decreases the required duration of treatment by 50%. The study of the time course effect of the process on bacterial morphology suggests that glidarc induces major alterations of the bacterial membrane. We showed that glidarc causes the release of bacterial genomic DNA. By contrast, an apparent decrease in the level of extractible lipopolysaccharide was observed; however, no changes in the electrophoretic pattern and cytotoxic activity of the macromolecule were noted. Analysis of extracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
43
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 29 publications
0
43
0
Order By: Relevance
“…[20][21][22][23] It has been reported that water treated by various plasma discharges becomes acidic, [9][10][11][20][21][22][23][24] which leads to antimicrobial effects. [9][10][11][24][25][26][27] The important question is which acid is created in water treated by plasma. Oehmigen et al [28] suggested that the acid created in water is nitric/nitrous acid and the antimicrobial properties observed are the result of synergetic action between H 2 O 2 and nitric/nitrous acid.…”
mentioning
confidence: 99%
“…[20][21][22][23] It has been reported that water treated by various plasma discharges becomes acidic, [9][10][11][20][21][22][23][24] which leads to antimicrobial effects. [9][10][11][24][25][26][27] The important question is which acid is created in water treated by plasma. Oehmigen et al [28] suggested that the acid created in water is nitric/nitrous acid and the antimicrobial properties observed are the result of synergetic action between H 2 O 2 and nitric/nitrous acid.…”
mentioning
confidence: 99%
“…However, since EthD-2 carries a net positive charge, we cannot rule out the possibility that EthD-2 may be recruited to the cell surface via electrostatic interaction with negatively charged species deposited by plasma (15). Alternatively, EthD-2 may stain nucleic acids leaking from the periphery of NTP-treated cells, as we and others have shown that plasma rapidly permeabilizes cell membranes and extracts intracellular nucleic acids (18). Prior to the onset of visible membrane damage, we observed only minor increases in DNA damage and protein oxidation, indicating that genetic damage and oxidative stress do not play primary roles in NTP-mediated microbial sterilization, consistent with the findings of other groups (7,26,27).…”
Section: Discussionmentioning
confidence: 99%
“…The hydroxyl radicals generated from APACP may contribute to membrane lipid peroxidation, causing an increase in membrane permeability (Ryu et al, 2013;Mai-Prochnow et al, 2014). It is evident from several related studies that the direct permeabilization of the cell membrane or wall is one of the modes of action in the toxicity of cold plasma for microbial cells (Kvam et al, 2012;Moreau et al, 2007).…”
mentioning
confidence: 99%